1991
DOI: 10.1161/01.atv.11.5.1166
|View full text |Cite
|
Sign up to set email alerts
|

Expression of monocyte chemotactic protein and interleukin-8 by cytokine-activated human vascular smooth muscle cells.

Abstract: The present study was designed to investigate the capacity of human vascular smooth muscle cells (SMCs) to produce a cytokine chemotactic for monocytes (monocyte chemotactic protein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
77
0
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(85 citation statements)
references
References 38 publications
3
77
0
4
Order By: Relevance
“…Thus, chemokines play a pivotal role in the development and complication of atheroma. Modified LDL and pro-inflammatory cytokines such as TNF␣, IL-1␤, IFN␥, or CD40 ligand induce chemokine expression in cells found in atheroma, such as EC, SMC, and M⌽ (31)(32)(33). However, knowledge of potential endogenous inhibitory mechanisms has lagged behind understanding of pro-inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, chemokines play a pivotal role in the development and complication of atheroma. Modified LDL and pro-inflammatory cytokines such as TNF␣, IL-1␤, IFN␥, or CD40 ligand induce chemokine expression in cells found in atheroma, such as EC, SMC, and M⌽ (31)(32)(33). However, knowledge of potential endogenous inhibitory mechanisms has lagged behind understanding of pro-inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine production from inflammatory cells has been well documented, but we and others have also shown in in vitro studies that smooth muscle cells can be potent sources of chemokines, including IL-8, MCP-1, RANTES, and MIP-1␣, when stimulated with proinflammatory cytokines. 36,52,53 These chemokines can also be produced by stimulated endothelial cells. 34,37,41,54,55 We have shown that cultured human VSMCs constitutively express mRNA for the chemokine receptors CCR-1 and CCR-2.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that MCP-1 is expressed in vitro by various cells such as macrophages, endothelial cells, and smooth muscle cells in response to various proinflammatory stimuli Wang et al, 1991). MCP-1 expression has been shown also in vivo such as within the atherosclerotic lesions of blood vessels from man, rabbits and hypercholesterolaemic primates or within synovial tissues from patients with rheumatoid arthritis (Nelken et al, 1991;Yla-Huttuala et al, 1991;Koch et al, 1992;Villiger et al, 1992;Yu et al, 1992).…”
Section: Introductionmentioning
confidence: 99%